2021
DOI: 10.1111/ane.13516
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities on the disability progression in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a chronic demyelinating neurological disorder predominantly affecting young adults. Based on the data of the MS Atlas 2020, there are 2.8 million people living with MS worldwide. 1 Investigation of the comorbidity burden in persons with MS (PwMS) has become increasingly important since studies have shown that co-occurring conditions may have negative effects on health outcomes in PwMS. 2-4 Among different comorbidity groups, cardiovascular diseases (CVD) are of particular interest be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Among 251 individuals with MS from Italy, a 1-point increase in the FRS was associated with an increased rate of reaching an EDSS score of 6 (HR 1.62; 1.22-3.01) ( 36 ). In a retrospective cohort of 2,725 individuals from Serbia, hypertension and diabetes were associated with a shorter time to reaching EDSS scores of 4, 6 and 7 ( 48 ). Uniquely, an Australian study examined the association between genetic polymorphisms associated with dyslipidemia and disability progression, allowing examination of the association between dyslipidemia and disability progression while limiting reverse causality ( 49 ).…”
Section: Effects Of Comorbiditiesmentioning
confidence: 99%
“…Among 251 individuals with MS from Italy, a 1-point increase in the FRS was associated with an increased rate of reaching an EDSS score of 6 (HR 1.62; 1.22-3.01) ( 36 ). In a retrospective cohort of 2,725 individuals from Serbia, hypertension and diabetes were associated with a shorter time to reaching EDSS scores of 4, 6 and 7 ( 48 ). Uniquely, an Australian study examined the association between genetic polymorphisms associated with dyslipidemia and disability progression, allowing examination of the association between dyslipidemia and disability progression while limiting reverse causality ( 49 ).…”
Section: Effects Of Comorbiditiesmentioning
confidence: 99%
“…Another study has reported increased prevalence of hypertension and ischemic heart disease in traumatic spinal cord injured patients compared with their controls and increased prevalence of diabetes and ischemic heart disease in amputees 19 . Disability progression in patients with multiple sclerosis is also associated with cardiovascular disease comorbidities 20 . However, to the best of our knowledge, few studies have comprehensively examined associations between different types of disability and heart disease per se, especially in populations at risk of cardiovascular disease such as people with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies observed that old age in MS is associated to a greater multimorbidity risk and, in turn, the presence of comorbidities, such as cardiovascular diseases, is considered a risk factor for disability accumulation (24,25). Age-associated comorbidities may also in uence the risk-bene t analysis for DMTs and be accompanied to reduced e cacy.…”
Section: Discussionmentioning
confidence: 99%